Formulasi dan Uji Karakterisasi Fisikokimia Gel Ekstrak Ranting Patah Tulang (Euphorbia tirucalli) - Nadya Ambarwati; Fajar Jamaluddin Sandhori; Annah Hubaedah (Journal of Pharmaceutical and Sciences, 2026)
Euphorbia tirucalli L. twigs contain various secondary metabolites, including alkaloids, flavonoids, tannins, saponins, and steroids, which have potential antibacterial activity. This study aimed to evaluate the effect of different concentrations of Euphorbia tirucalli twig extract on the physicochemical characteristics of gel formulations. Three gel formulations containing 15% (F1), 20% (F2), and 25% (F3) extract were prepared and evaluated for organoleptic properties, pH, spreadability, adhesiveness, homogeneity, and irritation potential. Quantitative data were analyzed using One-Way ANOVA at a 95% confidence level (α = 0.05). The results showed that all formulations produced homogeneous, semi-solid gels with a soft texture and did not cause skin irritation. The pH values ranged from 5.14 ± 0.193 to 5.67 ± 0.011, which were within the physiological skin pH range. The spreadability values ranged from 5.08 ± 0.310 to 5.19 ± 0.209 cm, meeting the acceptable criteria for topical gel preparations. All formulations exhibited good adhesiveness, with adhesion times exceeding 4 seconds (4.45 ± 1.673 to 4.46 ± 1.075 seconds). Statistical analysis indicated that variations in extract concentration had no significant effect on pH, spreadability, adhesiveness, homogeneity, or irritation parameters, with all p-values greater than 0.05. However, increasing extract concentration resulted in a visually darker gel color. In conclusion, all gel formulations fulfilled the physicochemical requirements for topical preparations, and extract concentrations ranging from 15% to 25% did not significantly affect the physicochemical characteristics of the gel, indicating their potential for further development as a natural topical dosage form.